The use of myofascial techniques (dry needle) for the treatment of maintained muscule contraction in peripheral facial palsy sequelae - ML Navarrete; ML Torrent; D Issa; J Salazar (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
Introduction: Based on the clinical and neurophysiologic similarities between the myofascial pain and the facial palsy's maintained muscle contraction, we considered treating the latter with dry needling the trigger points found in the physical examination. Objective: To assess the effect of dry needling as a method of treatment for the maintained muscle contraction, to improve pain and tightness as well as to facilitate movement.